2013
DOI: 10.1371/journal.pone.0054510
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Low-Abundance KRAS Mutations in Colorectal Cancer Using Microfluidic Capillary Electrophoresis-Based Restriction Fragment Length Polymorphism Method with Optimized Assay Conditions

Abstract: Constitutively active KRAS mutations have been found to be involved in various processes of cancer development, and render tumor cells resistant to EGFR-targeted therapies. Mutation detection methods with higher sensitivity will increase the possibility of choosing the correct individual therapy. Here, we established a highly sensitive and efficient microfluidic capillary electrophoresis-based restriction fragment length polymorphism (µCE-based RFLP) platform for low-abundance KRAS genotyping with the combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 56 publications
3
26
0
Order By: Relevance
“…The MCE system had a higher sensitivity, over 10-fold higher than that of the PAGE assay, as indicated in Fig. 5C-E. Like others have confirmed previously [47], the high sensitivity of the MCE system can reduce false-negative results in cancer diagnosis. Moreover, execution time and reagent consumption were significantly decreased compared to traditional analytic methods for disease monitoring.…”
Section: Performance Characteristics Of Microchip Electrophoresissupporting
confidence: 75%
“…The MCE system had a higher sensitivity, over 10-fold higher than that of the PAGE assay, as indicated in Fig. 5C-E. Like others have confirmed previously [47], the high sensitivity of the MCE system can reduce false-negative results in cancer diagnosis. Moreover, execution time and reagent consumption were significantly decreased compared to traditional analytic methods for disease monitoring.…”
Section: Performance Characteristics Of Microchip Electrophoresissupporting
confidence: 75%
“…Previous studies have shown that mutations in the KRAS gene, which leads to a change in KRAS sensitivity or elevated KRAS expression, are correlated with the development of various human cancers (van Grieken et al, 2013;Zhang et al, 2013). miRNA are trans-acting factors that function as regulators of cancer development, progression, and metastasis by binding to specific target genes, including KRAS.…”
Section: Discussionmentioning
confidence: 99%
“…As an example of what has been accomplished recently, micro CE integrated systems have been used for quantitative detection of low-abundance mutations of the KRAS gene from paraffin tissue sections of colorectal cancer. These systems have nano-liter sample introduction components leading to CE separation of the target genes and detection by laser-induced fluorescence (LIF); all being accomplished in minutes or even seconds (Zhang, et al, 2013;Xu, et al, 2010). DNA purification He and co-workers used capillary zone electrophoresis for purification of sequencing fragments (He, et al, 2000).…”
Section: Dna Sequencing and Mutation Detectionmentioning
confidence: 99%